Homoeoscelis meridionalis sp. nov. (Copepoda, Nicothoidae) parasitic on two cumaceans from southern South America with comments on its biology, and partial redescription of H. frigida Hansen, 1923 - Alberico, Natalia Andrea (2010)
The adult female and male, and the copepodite stage of the nicothoid copepod Homoeoscelis meridionalis sp. nov. are described. This parasite infests the branchial chambers of two closely related cumaceans from southern South America: Diastylis planifrons and D. fabrizioi. The maxilliped of the adult female of Homoeoscelis minuta is reillustrated, and the copepodite stage of H. frigida is briefly redescribed on the basis of their respective type materials. Of the 1768 specimens of Diastylis fabrizioi examined, 2.6% were found to be infested by Homoeoscelis meridionalis sp. nov. The copepod prevalence differs significantly between the female and male of D. fabrizioi (4.2 vs. 0.7%), and it was much higher in older instars of D. fabrizioi (adults and subadults) than in younger ones (juveniles and mancas) (7.1 vs. 0.3%).